Linking weather data, satellite imagery and field observations to household food production and child undernutrition: an exploratory study in Burkina Faso - Sorgho, R.; Franke, J.; Simboro, S.; Barteit, S.; Phalkey, R.; Sauerborn, R. (Horizon Research Publishing Corporation, 2017)
Worldwide, 50 million children under five are acutely malnourished, while 16 million amongst them suffer from severe wasting. Chronic malnutrition is more common and accounts for an estimated 159 million children, meaning that approximately 23.8% of all children under five worldwide are stunted. The proportion of stunted children has decreased worldwide between 1990 (39.6%) and 2014 (23.8%), but the progress has been unequal. While Asia as a whole reduced stunting by half (-47.0%) between 1990 and 2014, there are still 78 million stunted children in South Asia alone. Unlike Asia, the African continent has reduced stunting by just one quarter (24.0%). In contrast, the absolute number of stunted children in Africa has still increased, from 47 million in 1990, to 58 million in 2014. Under-nutrition is caused by a complex web of interdependent environmental/climatic, agricultural and socio-economic factors. Climate change has recently been identified as a major risk factor for childhood undernutrition. However, the scientific evidence base for this is weak. No study has so far simultaneously combined of the well-known drivers of undernutrition with climate change while being grounded in one population in one-time and in one location. Such studies are prerequisite for the relative attribution of the various risk factors, including climate chance, as causes of childhood undernutrition. In this exploratory study, methods from multiple sectors were applied to 20 randomly selected households in Bourasso in rural Burkina Faso, where more than 80% of the population are subsistence farmers, i.e. live off their fields. Well tested methods, such as household-level agricultural and nutritional surveys, anthropometric measurement of undernutrition with innovative methods, measuring household level-crop yields, were combined. This was done by participatory mapping of each household’s plots. Remote sensing algorithms were applied to RapidEye satellite scenes covering the study area in order to map the actual cultivated area and to derive qualitative harvest estimates for the surveyed micro-fields. Weather data were obtained from a research meteorological field station, about 20 km away from Bourasso. In addition to bringing field methods from different sectors together through the lens of a household, one further advanced method was integrated: The linkage between each household plot limits and their integration into the satellite scene making it possible to estimate crop yields at the plot level for each household and linking this to the nutritional status of that specific household. Thus the exploratory study produced the following results: High-resolution remote sensing data can assist studies on malnutrition in Burkina Faso; RapidEye is a promising data source in regard to the spatial resolution for micro-field assessments; The strong inter-annual variation of malnutrition is suggestive that climate is a casual factor in the absence of other explanatory factors (political unrest, price shocks of inputs, epidemics). Population-based studies replicating the described multi-sectoral toolbox should be upscaled to larger sample sizes and longer observational time series. This could contribute to generating crucial climate health impact functions, in this case for malnutrition.